OPTIMALISASI PEDOMAN DIET DAN POLA HIDUP SEHAT PENDERITA HIPERTENSI MELALUI PROLANIS - Sukamto, Ika Sumiyarsi; M. Sirojuddin Abbas, Maulana; Nadia Andarini, Maharani; Nabilah, Nada; Nurlaeli Putri, Pratiwi Perwirati; Rusdianto, Yusron Kurniawan (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2025)
Hypertension is a non-communicable disease that develops gradually and requires long-term management. The Prolanis program is implemented as a promotive and preventive effort to control this condition. This study aims to evaluate the improvement in knowledge of hypertensive patients after being given education on a healthy lifestyle. The activity was conducted at the Multipurpose Hall of RW 20, within the working area of Ngoresan Public Health Center, Surakarta City, using a pre-experimental one-group pre-test and post-test design. The intervention involved counseling sessions, educational leaflets, and interactive discussions provided to 30 Prolanis participants. The Wilcoxon test results showed a significant increase in knowledge after the intervention (p < 0.05). A total of 26 respondents showed an increase in post-test scores, while 4 remained the same. These findings indicate that counseling-based education is effective in enhancing the knowledge and attitudes of hypertensive patients, and supports disease control through lifestyle changes.